2005
DOI: 10.1037/0021-9010.90.2.232
|View full text |Cite
|
Sign up to set email alerts
|

Socialization Tactics, Employee Proactivity, and Person-Organization Fit.

Abstract: This study examined the linkage between organizational socialization tactics and person-organization (P-O) fit and examined the moderating influence of employees' proactivity behaviors. Results from a sample of 279 employee-supervisor pairs from 7 organizations in South Korea revealed a positive relationship between institutionalized socialization tactics and P-O fit perceptions. However, the association between firms' socialization tactics and P-O fit was facilitated or negated by several proactive behaviors … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

11
329
3
27

Year Published

2008
2008
2021
2021

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 343 publications
(370 citation statements)
references
References 41 publications
11
329
3
27
Order By: Relevance
“…But, they found that relationship building in regard to the employee-supervisor relationship negatively influenced the positive relationship between socialization tactics and P-O fit. Consistent with previous research (Bauer & Green, 1998;Ostroff & Kozlowski, 1993), these findings showed that different employee proactive behaviors can either hinder or enhance the socialization process, which calls for continued research on the effect of employee proactive behaviors during organizational and related outcomes (Kim et al, 2005). performance, commitment, and integration.…”
Section: Proactive Behavior Research and Socializationsupporting
confidence: 72%
See 4 more Smart Citations
“…But, they found that relationship building in regard to the employee-supervisor relationship negatively influenced the positive relationship between socialization tactics and P-O fit. Consistent with previous research (Bauer & Green, 1998;Ostroff & Kozlowski, 1993), these findings showed that different employee proactive behaviors can either hinder or enhance the socialization process, which calls for continued research on the effect of employee proactive behaviors during organizational and related outcomes (Kim et al, 2005). performance, commitment, and integration.…”
Section: Proactive Behavior Research and Socializationsupporting
confidence: 72%
“…In addition to its relationship with dispositional characteristics, proactive behavior has also been linked to a number of other organizational constructs such as self efficacy (Gruman et al, 2006;Ohly & Fritz, 2007), fit (Brett et al, 1990;Gruman et al, 2006;Kim et al, 2005), performance (Ashford & Black, 1996), socialization outcomes (Morrison, 1993), job design, leadership, and climate-related constructs (Bindl & Parker, 2010). As was stated earlier, many of these individual characteristics are often recognized as successful socialization outcomes.…”
Section: Proactive Behavior Research and Socializationmentioning
confidence: 98%
See 3 more Smart Citations